The Relationship Between Formula Feeding Patterns and Early Childhood Caries In Preschool Children In Ketileng Village, Todanan Blora - Wahyu Nur Zaini; Machmudah Machmudah; Zita Aprillia (Jurnal Kesehatan Gigi, 2023)
Caries that affects children under 72 months of age is called Early Childhood Caries (ECC). The high caries prevalence rate which reaches 81.5% in children aged 3-4 years is still a problem for Indonesia. One of the reasons for the high incidence of caries in preschoolers is the inappropriate pattern of breastfeeding or formula feeding. The purpose of this study was to analyze the relationship between patterns of formula feeding and ECC in preschool children in Ketileng Village, Todanan, Blora. This study used an analytic observational research design with a cross sectional approach. The research sample was 69 respondents using a purposive sampling technique. Data were obtained from the results of dental examinations using the PUFA index and a questionnaire filled out by parents/guardians of students. Data analysis used the chi square statistical test. The results of the study showed duration, duration, frequency of consumption of formula milk, use of bottles/pacifiers, addition of sweeteners to consumption of formula milk and history of breastfeeding up to 2 years of age, each of which showed a value of p 0.05, which means there is a relationship with ECC. The conclusion of this study is that there is a relationship between the pattern of formula feeding and the presence of ECC in preschool children in Ketileng Village, Todanan, Blora.